Facile and eco-friendly synthesis of chromeno[4, 3-b]pyrrol-4(1H)-one derivatives applying magnetically recoverable nano crystalline CuFe2O4 involving a domino three-component reaction in aqueous media. Issue 60 (8th June 2016) - Saha, Moumita; Pradhan, Koyel; Das, Asish R.
Abstract : Nanocrystalline CuFe2 O4 catalyzed one pot three component synthesis of chromeno[4, 3- b ]pyrrol-4(1 H )-one derivatives has been achieved in aqueous media. Abstract : Nanocrystalline CuFe2 O4 catalyzed one pot three component synthesis of chromeno[4, 3- b ]pyrrol-4(1 H )-one derivatives has been achieved in aqueous media. The reaction between the essential building blocks (amine, glyoxal monohydrate and 4-aminocoumarin) has been performed at low catalyst loading, leading to a high yield of the desired heterocyclic scaffold. CuFe2 O4 magnetic nanoparticles were prepared by a simple and effective citric acid complex method and characterized by using XRD, FT-IR, EDX and TEM and HRTEM images. The easy recovery and reusability of the catalyst and operational simplicity of the process makes the protocol attractive, sustainable, and economic.